2008
DOI: 10.2214/ajr.07.3599
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Carcinoma Update: Multimodality Imaging Evaluation, Staging, and Treatment Options

Abstract: Understanding the characteristic appearances of primary gallbladder carcinoma at multiple imaging modalities can facilitate diagnosis and enable more accurate staging for triage to extended resection or an alternate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 20 publications
2
111
2
3
Order By: Relevance
“…Female gender and advanced age are demographic risk factors for gallbladder carcinoma (15). In the present study, the male to female ratio was found to be 1:4 in patients with incidentally diagnosed gallbladder cancer, and the mean age of this group was significantly higher than the mean age of the remaining patients.…”
Section: Discussioncontrasting
confidence: 39%
“…Female gender and advanced age are demographic risk factors for gallbladder carcinoma (15). In the present study, the male to female ratio was found to be 1:4 in patients with incidentally diagnosed gallbladder cancer, and the mean age of this group was significantly higher than the mean age of the remaining patients.…”
Section: Discussioncontrasting
confidence: 39%
“…Gallbladder cancer should be suspected on ultrasonography if there is a mass lesion (40-65 %), a polyp of size >10 mm (15-25 %) and focal or diffuse asymmetric wall thickening (20-30 %) or a porcelain gallbladder with wall calcifications [27].The algorithm for management of GBC discovered incidentally during cholecystectomy for GSD is given in Fig. 1.…”
Section: Algorithmic Approach For Igbc Discovered During Cholecystectomymentioning
confidence: 99%
“…Though it is the most common cancer of the biliary tree, gallbladder (GB) cancer is a relatively uncommon gastrointestinal tract malignancy worldwide, and it has been known to be a lethal malignancy [1][2][3].…”
Section: Introductionmentioning
confidence: 99%